Diseminasi kelompok Karang Taruna Desa Pationgi dalam pembuatan Biofoam kemasan pengganti Styrofoam - Irna Erviana; Andi Muhammad Irfan Taufan Asfar; Andi Muhamad Iqbal Akbar Asfar; Muhamamd Safar; Sartika Sari Dewi; Wiwi Damayanti; Yulita Yulita (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2022)
Bio foam is an alternative packaging to replace Styrofoam made from natural raw materials such as starch, with the addition of fiber to strengthen its structure. Bio foam is a product that is not only biodegradable but also renewable. The raw material for packaging bio-foam in this service activity is peanut shell waste, a combination of rice husk waste. Peanut shell and rice husk waste are used as ingredients in manufacturing bio-foam because these materials contain high carbon elements, producing K-dots compounds that can benefit human life if processed. This service activity was carried out in Pationgi Village, Patimpeng District, Bone Regency, with three main stages: counseling, training, and mentoring. This community service activity aims to provide knowledge and skills to Karang Taruna Group partners in processing peanut shell waste and rice husks into environmentally friendly alternative packaging (bio-foam) as a substitute for Styrofoam. As a result of this community service, the Pationgi Village Youth Group partners now have more knowledge and skills about how to process nutshell and rice husk waste to make bio-foam packaging that is better for the environment and can be used instead of Styrofoam.